Developing Islamic Learning Media of Fable Box to Develop Students' Spiritual Quotient - Efendi, Efendi; Alkhaira, Syofia; Mutiaramses, Mutiaramses; Elkhaira, Indana; Monlinia, Yuyu (Khalifa Journal of Islamic Education, 2019)
This study aims to analyze the effectiveness of using Islamic Box Fabel learning media in fostering spiritual intelligence such as honesty, discipline, mutual cooperation, responsibility, motivation and courage towards students. The research was conducted with research and development (R&D) methods, this research approach is appropriate to use because it aims to develop media in a learning method. The research data was taken from 42 participants through an analysis of value documents in three elementary schools through three cycles of data retrieval. All data were then analyzed using SPSS Version 22.0 software. Overall the results of the study indicate that the use of Islamic Box Fable learning media is very effective to use in fostering the spiritual intelligence of students. Improved honesty, discipline, mutual cooperation, responsibility, motivation and courage obviously can be seen in every cycle that have been carried out. The results of this study have succeeded in revealing that there are many ways and methods that can be done by the teacher to deliver material or messages of learning in the classroom, one of which uses the Fable Box media as proposed by the researcher who conducted this study